2004
DOI: 10.1021/ma035633n
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Tension for the Structure of PEP−PEO Polymeric Micelles. A Combined SANS and Pendant Drop Tensiometry Investigation

Abstract: We investigated the influence of interfacial tension, γ, on the micellization properties of a highly asymmetric poly(ethylene-co-propylene)-poly(ethylene oxide) (PEP-PEO) block copolymer in mixed solvents consisting of water and dimethylformamide (DMF). Both are good solvents for PEO and nonsolvents for PEP but exhibit a large difference in γ with respect to the insoluble core block. Micellar characteristics were obtained by small-angle neutron scattering (SANS) and subsequent fitting of a coreshell form facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
141
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(149 citation statements)
references
References 37 publications
8
141
0
Order By: Relevance
“…Figure 2 shows that this theoretical model almost perfectly describes the growth behavior for the three concentrations with the same parameter set once allowing for slight variations within a few percent, reflecting stochastic minute variations in the experimental conditions. The fits yield a value of about 0 % 38:2 and a spread of less than 3% This corresponds to an effective microscopic interfacial tension % 19 mN=m that is of the same order as the measured macroscopic interfacial tension between PEP and this DMF-water mixture: % 12 mN=m [21]. For the other parameters we obtain % 1:35 AE 5%, c scal ¼ 2:777 Â 10 5 and f % 0:034 ms À1 yielding an asymptotic value for 1 of % 2 Â 10 À4 (0.02%) which is the critical micelle concentration (CMC).…”
Section: Prl 102 188301 (2009) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 69%
See 4 more Smart Citations
“…Figure 2 shows that this theoretical model almost perfectly describes the growth behavior for the three concentrations with the same parameter set once allowing for slight variations within a few percent, reflecting stochastic minute variations in the experimental conditions. The fits yield a value of about 0 % 38:2 and a spread of less than 3% This corresponds to an effective microscopic interfacial tension % 19 mN=m that is of the same order as the measured macroscopic interfacial tension between PEP and this DMF-water mixture: % 12 mN=m [21]. For the other parameters we obtain % 1:35 AE 5%, c scal ¼ 2:777 Â 10 5 and f % 0:034 ms À1 yielding an asymptotic value for 1 of % 2 Â 10 À4 (0.02%) which is the critical micelle concentration (CMC).…”
Section: Prl 102 188301 (2009) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 69%
“…The self-assembly process of a model amphiphilic block copolymer was triggered by an interfacial tension jump experiment by rapidly changing the solvent quality for one of the blocks. Using a detailed quantitative model, we further demonstrate that the kinetic pathway proceeds by unimer exchange where only single chains are added or removed at a time.As a model system, we employ a well-defined amphiphilic poly(ethylene-alt-propylene)-poly(ethylene oxide) (PEP1-PEO20, numbers indicate the approximate molecular weight in kg=mole) block copolymer [21]. Extensive previous studies have shown that these asymmetric PEP-PEO diblock copolymers form well-defined starlike micelles in water-dimethylformamide (DMF) solvent mixtures [7,8,21,22].…”
mentioning
confidence: 99%
See 3 more Smart Citations